THE AFRICAN STATE AND IMPLICATIONS OF HUMAN RIGHTS VIOLATIONS ON STATE STABILITY IN THE 21ST CENTURY: THE NIGERIAN AND SOUTH AFRICAN EXPERIENCE - Alozie, Cyprian C. (African Journal of Social and Behavioural Sciences, 2024)
This paper examined the incidence of human rights violations in Africa and its implications for state stability in the 21st century with a focus on Nigeria and South Africa. Some socioeconomic, cultural, religious and political factors have generally triggered human rights violations in Africa. State stability denotes the level of harmonious relationships that exist among the various actors, groups and organizations found in the state to the extent that putting all things together, the state pursues and realizes her aspirations or goals without much distractions. Human rights violations in Africa have negative implications not only for socioeconomic activities but also for state stability. The study is predicated on social contract theory. Methodologically, the paper relied on the documentary method for its data gathering and qualitative analysis for its data analysis. The study recommends among others; creation of more awareness and enlightenment on the essence of human rights observance by the state and its agencies; bringing to book in an unbiased and nonpartisan manner human rights violators. The paper concludes by urging the African State especially Nigeria and South Africa to take steps and strengthen those institutions set up to safeguard human rights for the overall improvement on state stability in Africa.